Sequence of the gene for isoleucine tRNA(1) and the surrounding region in a ribosomal RNA operon of Escherichia coli - Sekiya, Takao (1979)
A DNA fragment of about 2000 base pairs carrying the gene for tRNA(1)(Ile) has been cloned from a total Eco RI endonuclease digest of Escherichia coli DNA. Sequence analyses revealed that about the first 850 base pairs from one end of the fragment contain a nucleotide sequence corresponding to that in the 3'-end of 16S rRNA. The gene for tRNA(Ile) follows the 16S rRNA gene and both genes flank a spacer sequence of 68 base pairs. The spacer region contains a repeating, a hair pin and a symmetrical structure when the sequence is viewed in the single stranded form. A notable hair pin structure is also observed in the region adjacent to the 3'-end of the tRNA(1)(Ile) gene. In addition, about 850 base pairs from the other end of the DNA fragment have been found to contain the nucleotide sequence of the 5'-end of 23S rRNA. The presence of the genes for tRNA(1)(Ile), 16S and 23S rRNA and the hybridization to tRNA(1)(Ala) suggest that this cloned DNA is part of one of the E. coli rRNA operons carrying these two tRNA genes as a spacer.